2022
DOI: 10.3390/ijms232415526
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of MicroRNA Biomarkers in Equine Distal Interphalangeal Joint Osteoarthritis

Abstract: Osteoarthritis of the equine distal interphalangeal joint is a common cause of lameness. MicroRNAs from biofluids are promising biomarkers and therapeutic candidates. Synovial fluid samples from horses with mild and severe equine distal interphalangeal joint osteoarthritis were submitted for small RNA sequencing. The results demonstrated that miR-92a was downregulated in equine synovial fluid from horses with severe osteoarthritis and there was a significant increase in COMP, COL1A2, RUNX2 and SOX9 following m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…However, miRNAs, such as miR‐145‐5p and miR‐23b‐3p have been reported as prospective biomarkers for monitoring acute pain in equines (Lecchi et al., 2018 ). Not to mention, miRNA‐16 and miRNA‐125b were reported to be down‐regulated in OA synovial fluid samples and highly expressed in sarcoid tissue, respectively (Baker et al., 2022 ; Unger et al., 2019 ). Whilst a handful of these miRNAs have been shown to be immunomodulatory, the newly reported ones, such as miR‐21‐5p, miR‐27a‐3p, miR‐27b‐3p and miR‐143‐3p, serve as novel screening candidates for equine treatment.…”
Section: Resultsmentioning
confidence: 99%
“…However, miRNAs, such as miR‐145‐5p and miR‐23b‐3p have been reported as prospective biomarkers for monitoring acute pain in equines (Lecchi et al., 2018 ). Not to mention, miRNA‐16 and miRNA‐125b were reported to be down‐regulated in OA synovial fluid samples and highly expressed in sarcoid tissue, respectively (Baker et al., 2022 ; Unger et al., 2019 ). Whilst a handful of these miRNAs have been shown to be immunomodulatory, the newly reported ones, such as miR‐21‐5p, miR‐27a‐3p, miR‐27b‐3p and miR‐143‐3p, serve as novel screening candidates for equine treatment.…”
Section: Resultsmentioning
confidence: 99%
“…There are few studies on the EV protein cargo in synovial fluid-derived EVs in OA [23,24] and none in the horse. We formerly identified that differential expression of small nucleolar RNAs (snoRNAs) [25][26][27] and microRNAs [28,29] contributes to this imbalance, which isa key mechanism in OA. We require biomarkers to identify early OA before cartilage ECM is irreversibly degraded.…”
Section: Introductionmentioning
confidence: 99%